Bayesian Inference Supports the Use of Bypass Surgery Over Percutaneous Coronary Intervention To Reduce Mortality in Diabetic Patients with Multivessel Coronary Disease - Lang, Christopher D.; He, Yulei; Bittl, John A. (International Journal of Statistics in Medical Research, 2015)
Background: Coronary artery bypass graft (CABG) surgery may confer a survival advantage over percutaneous coronary intervention (PCI) in diabetic patients with multivessel coronary artery disease (CAD), but results of individual studies have been mixed. The primary aim of the current study was to compare mortality rates in diabetic patients with multivessel CAD randomized to either or CABG or PCI at 5 years or longest follow-up. Methods: Using a Bayesian approach, we updated a prior probability distribution elicited from 8 clinical trials (N=2024) with the likelihood obtained from the Future Revascularization Evaluation in Patients with Diabetes Mellitus: Optimal Management of Multivessel Disease (FREEDOM) (N=1460) to determine whether clinical trial evidence supports the underlying hypothesis that CABG is superior to PCI for diabetics with multivessel CAD. Results: A conjugate normal model comparing mortality rates favored the use of CABG (posterior mean odds ratio [OR] = 0.58, 95% Bayesian credible interval [BCI] = 0.48–0.71). Models weighted by the use of drug-eluting stents also favored the use of CABG over PCI (OR = 0.61, 95% BCI 0.48–0.78), as did models weighted by study age (OR=0.64, 95% BCI 0.52–0.80) or use of arterial conduits (OR=0.64, 95% BCI 0.51–0.81). The results were supported by a Bayesian hierarchical meta-analysis using a non-informative prior distribution (OR=0.55, 95% BCI 0.37–0.76). Conclusions: By integrating evidence from various studies, Bayesian methods directly support the underlying hypothesis that revascularization with CABG improves survival compared with PCI in diabetic patients with multivessel CAD.